Operations for calculating l1 and Frobenius norm
조회 수: 1 (최근 30일)
이전 댓글 표시
Hi all,
Imagine I have 2 same-length vectors, u1 and u2, and e = u1 - u2. I'd like to calculate 1. l1 norm of e; 2. Frobenius norm of e. In my case I cannot get e and calculate norm directly, so I did something like this for Frobenius norm:
clear; clc;
% test norm 1 and Frobenius norm, what's the equivalent transformation?
u1 = (1:5)';
u2 = u1 - 3;
e = u1 - u2;
%%calculate Frobenius norm directly.
enm2 = norm(e, 'fro');
%%calculate Frobenius norm indirectly
emtx = [u1 -u2];
emtxt = emtx' * emtx;
enmts = sqrt(sum(emtxt(:)));
My question is, can I do something similar for calculating l1 norm? If I get emtx = [u1 -u2], IS there a way to calculate l1 norm without obtaining e = u1 - u2?
Many thanks!
댓글 수: 0
답변 (1개)
Matt J
2017년 7월 12일
편집: Matt J
2017년 7월 12일
Since it's a homework problem, I'll just give you a hint. What does
sum(emtx.^2,2)+2*prod(emtx,2)
give you?
댓글 수: 7
Matt J
2017년 7월 13일
Well, the Frobenius norm and the l1 norm are the same when the dimension of emtx is 1, so whatever you are doing for the Frobenius norm case can be done for the l1 case for each emtx(i). Then you can just add them up...
참고 항목
카테고리
Help Center 및 File Exchange에서 Discrete Math에 대해 자세히 알아보기
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!